A configuração da prática como componente curricular nos cursos de licenciatura em Ciências Biológicas das Universidades Estaduais da Bahia - Brito, Luisa Dias (2011)
In this study, the curricular configurations designed by undergraduate teacher training courses in the Biological Sciences area of Bahia state universities to implement 400 hours of practice as a curricular component , according to the national Curricular Guidelines for teacher education (DCN), were investigated. The objective of this study was to understand those configurations of the course projects and identify the senses of practice, included in the DCN, which were mobilized for the production of such design. In addition, this study aimed at understanding the processes, conflicts, and disputes involved in this design process. This study was based on the policy cycle approach, a contribution to the analysis of educational policies, proposed by the British researcher Stephen Ball and his collaborators and also on Brazilian studies based on Ball‟s theories and which investigate the current national curricular policies for teacher education. This research was divided into two parts. Firstly, a documental analysis of the courses‟ designs was performed focusing on the identification of how the practice as a curricular component is configured in each design and which practice senses were actually mobilized. In the second part of the research, two of the courses evaluated were investigated through semi-structured interviews with teachers who were involved in the development process for the creation of a curricular space of practice as part of the curricular content. The goal was to identify the conflicts involved in the development of this process. Results: among the 6 projects analyzed, four respond to the DCNs recontextualizing the arguments that justify the special focus on practice in teacher training. In those projects, the practice space focuses on involving the undergraduate students seeking a teacher degree, from the beginning of the course, in the issues and problems related to the educational area in general and in specific areas of teaching, more specifically sciences and biology. Some ideas were recontextualized, for instance, the idea, according to DCN, that the experience the undergraduate students will have with numerous education spaces and/or the problematization of the issues related to professional practice would enable them to reinforce their education as teachers as well as to recognize the complexities inherent in teaching. The projects analyzed are aimed at promoting and articulating different practices from an interdisciplinary perspective focusing on procedures, readings, analyses, discussions, group work, reflexive processes and contact with different educational spaces. It was found that in the other two projects, the DCN argumentations were not mobilizing for the configuration of the curricular space under consideration. The analysis of the interviewee‟s responses indicated the arising of conflicts and the disputes involving the configuration of the curricular space of practice , which were based on the senses attributed to this space: a) in one of the courses, the debates were about whether the practice hours should be part of the specific area disciplines (biology) or they should have their own space in the curriculum; b) in the other course, the debates were about whether the practice should be the place where the undergraduate students would learn to transpose their specific knowledge into teaching science and biology or whether the role of practice as a curricular component would be problematizing issues inherent in professional practice and science and biology teaching. In sum, this study showed that practice as an education-related dimension, has been widely used in the context of undergraduate teacher training courses in Biological Sciences of Bahia state universities through a recontextualization of national curricular policies for teacher education (DCN).